Always on : digital brand strategy in a big data world - Øverland, Arve Peder (Gildan Audio, 2018)
Where do powerful strategies come from' How do some companies develop strategies that enable them to outperform others regardless of the state of their industry or the economic climate' How does a company get the essentials to work in regard to the company's strategies, such as leadership buy-in and follow through on implementations and performance management, without being slow, rigid and check-box focused' These are some of the questions asked by Arve Peder Overland in Always On: Digital Brand Strategy in a Big Data World. Companies have different needs and live in vastly different environments. The internal structure of an organization and the market in which it competes is not going to adapt to a digital strategy process, it must find a process and methodology that works best for it. With big data emerging as a standard framework for decision making, digital strategy and governance have taken on increased importance. It's a given in today's online marketplace that you are perceived as being always on. Make sure your governance programmes for your systems and platforms keep it that way. Think fast, be agile, be ready-you're always on!